P14.103 Patterns of diffuse glioma progression - Kobyakov, G L (Neuro Oncol, 2019)
BACKGROUND: According to WHO 2016 Classification, all gliomas are considered potentially malignant. Earlier it was thought that the ultimate goal for treatment is local control of tumor growth: maximal surgical resection with subsequent local radiotherapy +/- chemotherapy. Disease progression was primarily linked only to local relapse. In the recent years, different progression patterns of diffuse glioma were identified: from distant growth into an anatomically unrelated area far from primary lesion, to bone metastases and even to visceral organ metastases. MATERIAL AND METHODS: In this study we analyzed glioblastoma progression patterns in a cohort of 170 patients, who received radiation therapy as one of the treatment options for local relapse in Burdenko Neurosuregry Institute. All patients had a first relapse of glioblastoma at the age of 16 to 74 years old, 72 patients were female and 98 male. All patients initially underwent surgery and local radiotherapy (in combination with temozolomide) for a solitary supratentorial lesion of glioblastoma. Various methods of radiotherapy (including radiosurgery and hypofractionated radiation therapy) were used as one of the treatment options for recurrent tumor. One of our aims was to evaluate glioblastoma progression patterns in this cohort. RESULTS: Comparing neuroimaging data at the time of tumor progression with initial MRI we found that in 127 of 170 patients disease progression was identified anatomically close to the primary tumor site, i.e. disease progressed as a local relapse. Recurrent lesions without obvious anatomical relation to primary site were identified in 33 patients (19.4%); in particular, 7 patients had a lesion in contralateral hemisphere, one patient had spinal subarachnoid dissemination. A combination of local and distant tumor progression was identified in 10 of these 33 patients. CONCLUSION: We identified the following progression patterns for diffuse glioma based to these data and previous clinical experience: (a) local brain relapse - anatomically close to the primary lesion; (b) brain and spinal subarachnoid spread; (c) distant relapse - anatomically unrelated to primary tumor (can be both in ipsilateral or contralateral brain hemisphere); (d) local tumor progression as infiltration of soft tissues of the head and cranial bones; (e) regional lymph node metastases; (f) distant metastases - skeletal bone metastases and/or visceral organ metastases. Naturally, different combinations of these diffuse malignant glioma progression patterns are possible. A quite high incidence and differences between diffuse glioma progression patterns require a more thorough evaluation both because of treatment strategies as well as to understand the origins of glial tumors (e.g. Why in some cases of complete remission at the primary tumor site there is tumor progression in contralateral hemisphere?)